Parent Marginalization, Marginalized Parents: Creating a Place for Parents on the School Landscape - Pushor, Debbie; Murphy, Bill (Alberta Journal of Educational Research, 2004)
In this article we lay Debbie's research on the positioning of parents in relation to the school landscape alongside Bill's classroom work with Aboriginal parents. Our work challenges the view that parents are given place and voice in their children's schooling experiences. We question assumptions on which the term partnership is used with parents and argue that although many parents are positioned in marginalized ways in regard to their children's schooling, this situation is more pervasive for Aboriginal parents than for parents of the dominant culture. The narrative of Bill's home visit program and the telling of his home visit with Helen's mother create a new story of Aboriginal parental participation: a story that shifts thinking and practice.